Database CIAT FAO - Castro-Nuñez, Augusto Carlos; Sylvester, Janelle Marie; Gutiérrez, Diana; Pérez Marulanda, Lisset; Vanegas Cubillos, Martha Cristina; Castro-Llanos, Fabio Alexander (2022)
This file contains the collected data for all variables considered in the study (described on Variables_metadata_CIAT_FAO_2022.xlsx file) for 40 pantropical countries with a series of 18 years (2004-2021)